EP 134. Effect of transcranial random noise stimulation depends on sensitivity to sham stimulation. Issue 9 (September 2016) - Kortüm, V.; Brede, M.; Parkosadze, K.; Siniatchkin, M.; Moliadze, V.
Abstract : Introduction: Tranccranial random noise stimulation (tRNS) induces a consistent excitability increase lasting at least 60 min after 10 min of stimulation, as demonstrated by both physiological measures and behavioural Tasks (Terney et al., 2008 ). The present study tests whether the tRNS-induced changes in corticospinal excitability varies as a function of individual differences in sensitivity to sham stimulation. Methods: The study was approved by the Ethic Committee of the Faculty of Medicine Christian-Albrechts University Kiel. 24 participants, aged between 18 and 30 years, participated in the study. All subjects were right-handed according to the Edinburgh handedness inventory (Oldfield, 1971 ). Stimulation techniques : tRNS (1 mA, 10 min) was applied through a pair of saline-soaked surface sponge electrodes (5 × 7 cm). The minimum period between sessions for a single subject was 7 days, and sessions were applied in randomized order. Monitoring of motor cortical excitability: To examine changes in corticospinal excitability, motor evoked potentials (MEPs) of the right first dorsal interosseous muscle (FDI) were recording following stimulation of its motor-cortical representation field by single-pulse TMS. For further analysis we divided three subgroups according to excitatory ('Excitatory group', n  = 9), inhibitory ('Inhibitory group', n  = 7) or no respond ('Non responder group', n  = 8) to sham- stimulation (Wilcoxon signed-rank test for dependent sampling). For this, we compared the MEP-amplitude in mean of the three time points after stimulation with the MEP-amplitude in mean before. Results: In all subjects the tRNS was well tolerated. The general finding of present study is that sensitivity to sham stimulation has impact on effect of tRNS; namely, 'Excitatory group' resulted in inhibition of tRNS, whereas inhibitory group shows excitation of tRNS. For 'Non responder group' the 1 mA tRNS resulted in a significant increase of MEP amplitudes compared to sham stimulation, which is consistent with the literature Conclusion: Accounting for variation in individual sensitivity to sham stimulation, stimulation may influence the utility of tRNS as a tool for understanding brain-behavior interactions and as a method for clinical interventions.